KONTROL DIRI DAN KECEMASAN KOMUNIKASI INTERPERSONAL PADA PRAMUWISATA - Nurul Huda; Basuki Basuki; Sigit Tri Pambudi (Jurnal Ilmu Komunikasi, 2009)
This study aim to analysis relationship of self-control and anxiety of interpersonal communication in a tourist guide. Product moment corelation analysis (rxy) yields for 0905, to prove the relationship between self-control and interpersonal communication anxiety in a tourist guide. These results indicate a negative relationship between the variables X (Self Control) and variable Y (Interpersonal Communication Anxiety in the guides). Social Learning Theory became a theories used in this study, where most of the individual behavior acquired partly the result of learning through observation of behavior displayed other individuals whose became the model. Elaboration Likelihood Theory which states that each individual will interpret the message or information they receive, in accordance with the information they have and their beliefs about something related to the message. Self-control on the tour guides in Yogyakarta based on the five major aspects of self-control, that has a very high level of measurement. Includes the ability to anticipate events, the ability to interpret events and the ability to take decisions. Meanwhile, two other aspects of self control shows the results of measurements at very low category, which consists of aspects of behavior and stimulus control. While anxiety based on the three aspects of interpersonal communication, which consists of inhibition of the ability to express themselves, lack of interest in communicating and social interaction is interrupted, it indicates the level measurement at very low category. Thus, interpersonal communication anxiety on tour guides in Yogyakarta can be said to be very low.